2020
DOI: 10.1186/s13063-020-04931-w
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the “promising zone” design

Abstract: Introduction Sample size calculations require assumptions regarding treatment response and variability. Incorrect assumptions can result in under- or overpowered trials, posing ethical concerns. Sample size re-estimation (SSR) methods investigate the validity of these assumptions and increase the sample size if necessary. The “promising zone” (Mehta and Pocock, Stat Med 30:3267–3284, 2011) concept is appealing to researchers for its design simplicity. However, it is still relatively new in the application and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The most commonly used CP assumptions are (1) current trend ( ; assuming the data observed so far is likely to continue for the duration of the trial), sometimes referred to as ‘observed conditional power’ [ 8 ] and (2) the hypothesised treatment effect ( ; assuming the hypothesised treatment effect used in the original sample size calculation), sometimes referred to as ‘assumed conditional power’ [ 8 ]. There is criticism in the literature regarding the current trend assumption, due to high variability early in the trial duration and potentially yielding an unstable estimate of conditional power values [ 6 ]. An alternative recommendation from the literature [ 7 , 9 ] is based on optimistic confidence limits of the observed treatment effect, being the single optimistic value of the two confidence limits defined by , where represents the percentage point of a standard normal distribution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly used CP assumptions are (1) current trend ( ; assuming the data observed so far is likely to continue for the duration of the trial), sometimes referred to as ‘observed conditional power’ [ 8 ] and (2) the hypothesised treatment effect ( ; assuming the hypothesised treatment effect used in the original sample size calculation), sometimes referred to as ‘assumed conditional power’ [ 8 ]. There is criticism in the literature regarding the current trend assumption, due to high variability early in the trial duration and potentially yielding an unstable estimate of conditional power values [ 6 ]. An alternative recommendation from the literature [ 7 , 9 ] is based on optimistic confidence limits of the observed treatment effect, being the single optimistic value of the two confidence limits defined by , where represents the percentage point of a standard normal distribution.…”
Section: Methodsmentioning
confidence: 99%
“…A futility boundary of 10% conditional power value is considered for CP assumption comparison in this re-analysis, although other values may be chosen, with boundaries between 10 and 40% being observed in the literature [ 2 , 9 ]. The smaller value has been chosen for this re-analysis to accommodate sample size re-estimation rules based on CP decisions, with alterations to sample size often occurring below 40% CP [ 3 , 6 ]. CP is calculated after every patient for illustrative purposes of CP during the trial progression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design approach described here may also be applied to settings allowing for a more nuanced classification of the study outcome. 25 Here P H 0 ð Þ and P H 1 ð Þ represent the prior probabilities of the design hypotheses about the trial primary endpoint. Their ratio…”
Section: Bayesian Inference Quantifies Evidence About Clinical Trial ...mentioning
confidence: 99%
“…When Bayesian inference is used, the study outcome is positive when the posterior probability of the treatment effect exceeding a pre‐specified clinically relevant threshold is much greater than the prior, with typical thresholds exceeding 95%. The design approach described here may also be applied to settings allowing for a more nuanced classification of the study outcome 25 …”
Section: Bayesian Inference Quantifies Evidence About Clinical Trial ...mentioning
confidence: 99%